Interrelationship of bottom fauna, fish and fisheries of Gobindsagar Reservoir, Himachal Pradesh - Koushal, D K (Indian Journal of Fisheries, 2011)
Benthic interaction among the communities with reference to fish was determined in Gobindsagar, an impoundment across the river Sutlej. The material for investigation of intestinal contents of Cyprinus carpio and Labeo calbasu was obtained from the three main ecological environments of the reservoir The analyses were combined with a study of benthos from the same environment. Conclusions drawn were that availability of benthos regulates the feeding behaviour of Cyprinus carpio and Labeo calbasu. Under prevailing conditions both these species have a selectivity for dipterans, especially larvae and pupae of chironomids. The wide water level fluctuation affecting bathymetric distribution of benthos led to change in availability of benthos and consequently had an influence on the trophic spectrum of the carp. Greater landings of Cyprinus carpio from zone II and I were primarily due to more availability of benthos coupled with other environmental factors.